Mobility of antimicrobial resistance across serovars and disease presentations in non-typhoidal Salmonella from animals and humans in Vietnam. - Bloomfield, Samuel; Duong, Vu Thuy; Tuyen, Ha Thanh; Campbell, James I; Thomson, Nicholas R; Parkhill, Julian; Le Phuc, Hoang; Chau, Tran Thi Hong; Maskell, Duncan J; Perron, Gabriel G; Ngoc, Nguyen Minh; Vi, Lu Lan; et al. (Microbiology Society, 2022)
Non-typhoidal Salmonella (NTS) is a major cause of bacterial enterocolitis globally but also causes invasive bloodstream infections. Antimicrobial resistance (AMR) hampers the treatment of these infections and understanding how AMR spreads between NTS may help in developing effective strategies. We investigated NTS isolates associated with invasive disease, diarrhoeal disease and asymptomatic carriage in animals and humans from Vietnam. Isolates included multiple serovars and both common and rare phenotypic AMR profiles; long- and short-read sequencing was used to investigate the genetic mechanisms and genomic backgrounds associated with phenotypic AMR profiles. We demonstrate concordance between most AMR genotypes and phenotypes but identified large genotypic diversity in clinically relevant phenotypes and the high mobility potential of AMR genes (ARGs) in this setting. We found that 84 % of ARGs identified were located on plasmids, most commonly those containing IncHI1A_1 and IncHI1B(R27)_1_R27 replicons (33%), and those containing IncHI2_1 and IncHI2A_1 replicons (31%). The vast majority (95%) of ARGS were found within 10 kbp of IS6/IS26 elements, which provide plasmids with a mechanism to exchange ARGs between plasmids and other parts of the genome. Whole genome sequencing with targeted long-read sequencing applied in a One Health context identified a comparatively limited number of insertion sequences and plasmid replicons associated with AMR. Therefore, in the context of NTS from Vietnam and likely for other settings as well, the mechanisms by which ARGs move contribute to a more successful AMR profile than the specific ARGs, facilitating the adaptation of bacteria to different environments or selection pressures.
Keywords: Antimicrobial resistance; Salmonella; chromosome arrangements; insertion sequences; plasmids; Animals; Anti-Bacterial Agents; Drug Resistance, Bacterial; Humans; Salmonella; Serogroup; Typhoid Fever; Vietnam